The Use of Toll-Like Receptor Agonists in HIV-1 Cure Strategies - Martinsen, Janne Tegder; Gunst, Jesper Damsgaard; Højen, Jesper Falkesgaard; Tolstrup, Martin; Søgaard, Ole Schmeltz (Frontiers in Immunology, 2020)
Toll-like receptors (TLRs) are a family of pattern recognition receptors and part of the first line of defense against invading microbes. In humans, we know of 10 different TLRs, which are expressed to varying degrees in immune cell subsets. Engaging TLRs through their specific ligands leads to activation of the innate immune system and secondarily priming of the adaptive immune system. Because of these unique properties, TLR agonists have been investigated as immunotherapy in cancer treatment for many years, but in recent years there has also been growing interest in the use of TLR agonists in the context of human immunodeficiency virus type 1 (HIV-1) cure research. The primary obstacle to curing HIV-1 is the presence of a latent viral reservoir in transcriptionally silent immune cells. Due to the very limited transcription of the integrated HIV-1 proviruses, latently infected cells cannot be targeted and cleared by immune effector mechanisms. TLR agonists are very interesting in this context because of their potential dual effects as latency reverting agents (LRAs) and immune modulatory compounds. Here, we review preclinical and clinical data on the impact of TLR stimulation on HIV-1 latency as well as antiviral and HIV-1-specific immunity. We also focus on the promising role of TLR agonists in combination strategies in HIV-1 cure research. Different combinations of TLR agonists and broadly neutralizing antibodies or TLRs agonists as adjuvants in HIV-1 vaccines have shown very encouraging results in non-human primate experiments and these concepts are now moving into clinical testing.